Highly sensitive detection of driver mutations from cytological samples and cfDNA in lung cancer. (7th October 2021) - Fujita, Kazutaka; Nakayama, Masayuki; Sata, Masafumi; Nagai, Yoshiaki; Hisata, Shu; Mato, Naoko; Suzuki, Takuji; Bando, Masashi; Hizawa, Nobuyuki; Hagiwara, Koichi
Abstract: Background: Bronchoscopy is a minimally invasive procedure for establishing the diagnosis of lung cancer. It sometimes fails to obtain tissue samples but readily collects cytological samples. Methods: We developed PNA‐LNA dual‐PCR (PLDP), which amplified mutant sequences by a high‐fidelity DNA polymerase in the presence of a peptide nucleic acid (PNA) oligomer having a wild‐type sequence. Mutations are detected either by locked nucleic acid (LNA) probes for quick detection of a limited number of mutations, which are EGFR, KRAS, and BRAF mutations in the current study, or by direct sequencing for a comprehensive screening. In a total of 233 lung cancer samples, the results for cytological samples by PLDP were compared with those for tissue samples by cobas® EGFR mutation test (cobas) or by the PNA‐LNA PCR clamp method (P‐LPC). Moreover, the performance of PLDP using cell‐free DNA (cfDNA) was investigated. Results: Peptide nucleic acid‐LNA dual‐PCR was able to detect each synthesized mutant sequence with high sensitivity. PLDP detected EGFR mutations in 80 out of 149 clinical samples, while the cobas or the P‐LPC detected in 66 matched. The correctness of PLDP was confirmed both by clinical response and by the results of sequencing using a next‐generation sequencer. PLDP detected mutations from cfDNA in approximately 70% of patients who harbors mutations in the tumor. Conclusions: Peptide nucleic acid‐LNA dual‐PCR exhibited an excellent performance, even using cytological samples. PLDP is applicable for the investigation of cfDNA. The combination of bronchoscopy and PLDP is attractive and will expand the utility of bronchoscopy in clinical practice. Abstract : Peptide nucleic acid‐LNA dual‐PCR sensitively detects mutations from cytological samples or cell‐free DNA in lung cancer. It will expand the utility of cytological specimens in clinical settings where bronchoscopy is employed.